Efektivitas Teh Celup Daun Bidara Laut Kombinasi Bubuk Kayu Manis sebagai Antidiare pada Mencit - Hasma Hasma Bakkareng; Rahmatullah Muin; Andi Nurpati Panaungi; Yusnita Usman (Rumah Sakit Ibnu Sina, Makassar, 2025)
Diarrhea is characterized by increased defecation frequency and altered stool consistency. Castor oil (Oleum ricini) induces diarrhea mainly through ricinoleic acid, which enhances intestinal secretion and motility. Sea bidara leaves (Ziziphus mauritiana) and cinnamon (Cinnamomum burmannii) contain tannins, flavonoids, and aromatic constituents (e.g., cinnamaldehyde) that may contribute to antidiarrheal activity. To evaluate the antidiarrheal effect of a combined sea bidara–cinnamon tea bag preparation in male Swiss Webster mice. An experimental study was conducted using 15 mice (n=3/group): negative control (castor oil + distilled water), positive control (loperamide), and three tea infusion groups—F1 (90%:10%), F2 (25%:75%), and F3 (50%:50%). Mice were fasted for 8 h, induced with castor oil (0.5 mL/20 g BW), and treated by oral gavage 30 min after induction. Observations were recorded at 30, 60, 90, and 120 min post-treatment. The primary Endpoint was total bowel movement (BM) frequency over 0–120 min. The secondary Endpoint was a standardized ordinal stool consistency score (0–3; 0=no BM, 1=formed, 2=soft, 3=watery/mucoid). Data were analyzed using Kruskal–Wallis with appropriate post-hoc testing (α=0.05) and effect size reporting. Significant between-group differences were observed in total BM frequency (H=10.24; p=0.0366; ε²=0.624) and stool consistency scores (H=11.74; p=0.0194; ε²=0.774). Descriptively, F3 showed the lowest total BM frequency, while F2 demonstrated faster cessation of BMs after 60 min. The combined sea bidara–cinnamon tea bag infusion exhibited antidiarrheal activity in the castor oil model; findings should be interpreted as preliminary due to the pilot sample size.